A molecular analysis to assess codling moth Cydia pomonella L. (Lepidoptera: Tortricidae) predation by orchard birds - Mangan, Anna M., author; Piaggio, Antoinette J., author; Hopken, Matthew W., author; Werner, Scott J., author; Pejchar, Liba, author; DigitalCommons@University of Nebraska - Lincoln, publisher (Colorado State University. Libraries, 2018)
The codling moth Cydia pomonella L. (Lepidoptera: Tortricidae) is a major economic pest in organic apple orchards. Observational methods, prey removal experiments and correlative experiments with exclosures or nest boxes have demonstrated that birds contribute to the removal of this insect pest. However, the majority of research conducted in the last several decades has taken place outside of the United States and methods for studying biological pest control have advanced dramatically and now include molecular techniques. We conducted a proof-of-concept study to test a DNA-based approach to detect C. pomonella prey in the diets of birds occupying organic apple orchards. We tested published Tortricidae primers, polymerase chain reaction (PCR) and sequencing for detection of C. pomonella in avian feces. We also tested the quality of DNA isolated and purified from fecal samples using two DNA extraction kits. Finally, we field-tested this tool to identify the presence or absence of C. pomonella in the laboratory and from field samples. C. pomonella DNA was amplified in less than 1% of field samples and was successfully sequenced in 0.5%. A single species, the brown-headed cowbird Molothrus ater (Boddaert), had fecal samples positive for C. pomonella DNA. While our results do not provide evidence that birds play a strong role in the control of C. pomonella in western Colorado organic apple orchards, the approach we present is a new tool for understanding bird-mediated ecosystem services, avian feeding ecology, and supporting management decisions for sustainable agricultural practices and farmland biodiversity.
Keywords: molecular scatology; bird diets; pest control; PCR; organic apples; agroecosystems